Ferroptosis, a Potential Therapeutic Target in Alzheimer’s Disease - Chen, Kai; Jiang, Xiaobing; Wu, Moxin; Cao, Xianming; Bao, Wendai; Zhu, Ling-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Cell death is a common phenomenon in the progression of Alzheimer’s disease (AD). However, the mechanism of triggering the death of neuronal cells remains unclear. Ferroptosis is an iron-dependent lipid peroxidation-driven cell death and emerging evidences have demonstrated the involvement of ferroptosis in the pathological process of AD. Moreover, several hallmarks of AD pathogenesis were consistent with the characteristics of ferroptosis, such as excess iron accumulation, elevated lipid peroxides, and reactive oxygen species (ROS), reduced glutathione (GSH), and glutathione peroxidase 4 (GPX4) levels. Besides, some ferroptosis inhibitors can relieve AD-related pathological symptoms in AD mice and exhibit potential clinical benefits in AD patients. Therefore, ferroptosis is gradually being considered as a distinct cell death mechanism in the pathogenesis of AD. However, direct evidence is still lacking. In this review, we summarize the features of ferroptosis in AD, its underlying mechanisms in AD pathology, and review the application of ferroptosis inhibitors in both AD clinical trials and mice/cell models, to provide valuable information for future treatment and prevention of this devastating disease.